From Jidāl to Digital Literacy: The Musa–Khidir Dialogue in QS. Al-Kahfi [18]: 60–82 as a Model for Addressing Misinformation and Hoaxes - Achmad Moehammad Fikrudh Dhuha; Moh. Akib; Mohamad Zaenal Arifin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study examines the jidāl method in the dialogue between Prophet Musa and Prophet Khidir in QS. Al-Kahfi [18]: 60–82 and its relevance to contemporary digital literacy challenges. Employing a qualitative library research approach, this study analyzes Qur’anic verses, classical and contemporary tafsir literature, as well as scholarly works on digital literacy, misinformation, and information ethics. The findings reveal that the jidāl method in the Musa–Khidir narrative is not merely a form of dialogue but an epistemological process that cultivates intellectual humility, contextual understanding, critical inquiry, and epistemic patience. The narrative demonstrates that premature judgments often arise from limited information and inadequate contextualization, conditions that closely resemble the mechanisms through which misinformation and hoaxes spread in digital environments. Through a Maqashid Syariah perspective, particularly the principle of ḥifẓ al-‘aql, the study argues that the narrative contributes to the preservation and development of human intellect by encouraging verification, reflective thinking, and wisdom-oriented judgment. Based on these findings, the study formulates a Qur’anic Digital Literacy Model consisting of three interconnected stages: verification (tabayyun and tatsabbut), clarification through constructive dialogue (jidāl ḥakīm), and transformation toward wisdom (ḥikmah). The study contributes theoretically to the intersection of Qur’anic studies, Maqashid Syariah, and digital literacy scholarship while providing practical insights for developing ethical and responsible information behavior in the digital age.